Application of fuzzy integrated FMEA with product lifetime consideration for new product development in flexible electronics industry - Kelvin P. L. Pun; Jason Rotanson; Chee-wah Cheung; Alan H. S. Chan (Journal of Industrial Engineering and Management (JIEM), 2019)
Purpose: the aim of this paper is to minimize the risks of new product development and shorten time-to-market, particularly for high-tech enterprise where the complexity of the product generate vast amount of failure mode. Design/methodology/approach: first, the concept of Critical Consideration Factor (CCF) is introduced based on product-specific technical characteristics, expected lifetime, and yield requirement to identify and prioritize the critical failure mode in the subsequent Failure Mode and Effect Analysis (FMEA), followed by process characterization on the high risk failure mode and Critical Parameter Management (CPM) practice to realize a robust mass production system of the developed technology. The application on the development of advanced flexible substrate and surface finishes fabrication technique is presented. Findings: through the proposed methodology, the risk level of each potential failure mode can be accurately quantified to identify the critical variables. With process characterization, reliability of the product is ensured. Consequently, significant reduction in development resources and time-to-market can be achieved. Practical implications: the development strategy allows high tech enterprises to achieve a balanced ecosystem in which value created through adaption of new technology/product can be thoroughly captured through commercialization in a timely manner with no field failure. Originality/value: the proposed development strategy utilizes a unique approach with thorough considerations that enables high tech enterprise to deliver new product with rapid time-to-market without sacrificing product lifetime reliability, which is key to achieve competitive advantage in the highly dynamic market.
Keywords: 650; New product development; risk management; failure mode and effect analysis; critical parameter management; advanced manufacturing; industry 4.0